EFFECT OF NEONICOTINOID INSECTICIDES ON PREDATORY COCCINELLIDS IN COWPEA AND GREEN GRAM - MITHU ANTU; D. M. KORAT; P. M. SANGLE (The Bioscan, 2015)
Field experiments were conducted during summer and kharif, 2013 to investigate the effect of neonicotinoid insecticides on predatory coccinellids in cowpea and green gram. The population of predatory coccinellids recorded at weekly intervals in all the treatments of neonicotinoid insecticides viz., imidacloprid, thiamethoxam and acetamiprid as seed treatment (ST) alone and in combination with one (at 30 days after germination (DAG)) or two (at 30 and 45 DAG) foliar sprays showed non-significant results during both seasons. Hence, these insecticides are safer to the predatory coccinellids in cowpea and green gram. However, relatively lower population of the coccinellids were recorded in the combination treatments (ST combined with one or two foliar sprays) than ST alone. Among the sole treatments (ST alone), highest number of coccinellids were found in acetamiprid followed by imidacloprid and thiamethoxam and the similar trend was observed in case of ST combined with foliar spray at 30 DAG and ST combined with foliar spray at 30 and 45 DAG indicating that acetamiprid was more safer to the coccinellids followed by imidacloprid and thiamethoxam.